Chemical Control of Morning Glory Species in Sugarcane Harvested in the Dry and Semi-Wet Seasons1 - CORREIA,N.M. (2016)
ABSTRACT The control of morning glory (Ipomoea spp. and Merremia aegyptia) was evaluated in five commercial sugarcane-production fields receiving applications of the herbicides sulfentrazone (0.9 kg ha-1), amicarbazone (1.4 kg ha-1), imazapic (0.147 kg ha-1), and hexazinone + tebuthiuron (0.325 + 0.75 kg ha-1) applied pre-emergence in either the dry season (July and August) or in the semi-wet season (early October); mesotrione alone (0.192 kg ha-1) or in combination (0.12 kg ha-1) with atrazine (1.5 kg ha-1) or diuron + hexazinone (0.491 + 0.139 kg ha-1) applied post-emergence in the wet season (November), and the phytointoxication of the chemical treatments for sugarcane. Five species of morning glory (Ipomoea hederifolia, Ipomoea nil, Ipomoea quamoclit, Ipomoea triloba and Merremia aegyptia) were assessed in the experiments. The applications during the dry, semi-wet, and wet seasons resulted in similar levels of control of I. hederifolia, I. nil, I. quamoclit, and I. triloba. The herbicides imazapic and mesotrione alone resulted in lower levels of control of M. aegyptia. Imazapic and the combination of mesotrione + (diuron + hexazinone) caused greater visible phytotoxicity to sugarcane than other herbicides applied during the dry and semi-wet seasons. However, the greatest loss of production was attributed to amicarbazone.